Concise Review: Balancing Stem Cell Self‐Renewal and Differentiation with PLZF. (5th January 2016) - Liu, Tong Ming; Lee, Eng Hin; Lim, Bing; Shyh‐Chang, Ng
Abstract : In recent years, the highly conserved promyelocytic leukemia zinc finger (PLZF, also known as ZBTB16, ZNF145) has attracted attention as a multifunctional transcription factor involved in major biological processes during development. As a transcription factor, PLZF shows tight regulation in its cell‐type‐specific and stage‐specific expression patterns. Emerging evidence shows that PLZF regulates the balance of self‐renewal and differentiation in stem cells. However, the gene regulatory network of PLZF is only beginning to be understood. In this review, we discuss the diverse functions of PLZF, in particular its role in self‐renewal versus differentiation of stem cells. We also discuss the current state of knowledge on the gene regulatory network of PLZF, in conjunction with its upstream factors, post‐translational modifications and binding cofactors for multiprotein complexes. This review aims to provide the reader with an in‐depth understanding of the molecular mechanisms underlying PLZF and the potential applications in tissue regeneration. Stem Cells 2016;34:277–287